2020
DOI: 10.21203/rs.2.18907/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HOXB4 promotes the malignant progression of ovarian cancer via DHDDS

Abstract: Background : Homeobox B4 (HOXB4) is correlated with poor prognosis of various cancer types.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…HOXB4, a member of the Antp homeobox protein family, regulates embryonic development and participates in tumor progression as an oncogene or tumor suppressor gene. In ovarian cancer, the expression of HOXB4 was closely related to poor prognosis and transcriptionally activated DHDDS to stimulate the proliferation and invasion of tumor cells 23 . Other studies also revealed that HOXB4 was upregulated in ovarian cancer cells and drug-resistant cells 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HOXB4, a member of the Antp homeobox protein family, regulates embryonic development and participates in tumor progression as an oncogene or tumor suppressor gene. In ovarian cancer, the expression of HOXB4 was closely related to poor prognosis and transcriptionally activated DHDDS to stimulate the proliferation and invasion of tumor cells 23 . Other studies also revealed that HOXB4 was upregulated in ovarian cancer cells and drug-resistant cells 35 .…”
Section: Discussionmentioning
confidence: 99%
“…HOXB4, the positive regulator implicated in the self-renewal of hematopoietic stem cells (HSCs) 21 , has been recognized as an oncogene or a tumor suppressor gene, depending on the specific type of cancer. HOXB4 was overexpressed in many cancers, including ovarian cancer 22,23 , cervical cancer [24][25][26][27] , lung cancer 28 , renal cancer 29 , mesothelioma 30 , and leukemia [31][32][33][34] , which promoted tumor growth and metastasis 23 . Moreover, increased HOXB4 expression resulted in drug resistance 31,35 .…”
Section: Introductionmentioning
confidence: 99%
“…PPP1CC plays an important role in regulating the GPCR signaling pathways 34 . HOXB4 can induce the expansion of hematopoietic and promote the malignant progression of ovarian cancer 35, 36 . Arg1 is related to the tumor-associated macrophage and inflammation resolution 37 .…”
Section: Discussionmentioning
confidence: 99%